Antibacterial effect of a hyperosmotic solution containing sorbate and ethanol on Enterococcus faecalis in planktonic form and as biofilm: an in vitro study. / Efecto antibacteriano de una solución hiperosmótica a base de sorbato y etanol sobre Enterococcus faecalis en forma planctónica y como biofilm: estudio in vitro. - Rojas Briones, Mónica Elizabeth; Oliva Rodríguez, Ricardo; González Ortega, Omar; González Amaro, Ana María; Mariel Cárdenas, Jairo; Avelar González, Francisco Javier; Guerrero Barrera, Alma Lilián (Investigación Clínica, 2020)
Abstract. The antibacterial effect of a hyperosmotic solution containing sorbate and ethanol on E. faecalis in planktonic state and in biofilm was evaluated. Three hyperosmotic solutions (HS-A, HS-B y HS-C) were obtained from different formulations of potassium sorbate and sodium chloride, which were tested as antimicrobials against planktonic forms of E. faecalis, in McFarland standards from 0.5 to 7, using the sedimentation technique and colony forming units (CFU) count. Afterwards an E. faecalis biofilm was produced in the palatal roots of upper first molars, by a static method in 21 days; subsequently they were prepared biomechanically by the Universal Protaper system, using the hyperosmotic solution B as an irrigant to evaluate the bacterial load reduction. One pre-instrumentation sample and one post-instrumentation sample were taken, and then were processed and cultivated to count CFU. Consecutively, roots were observed by scanning electron microscopy. The hyperosmotic solution had an important antibacterial effect when used against E. faecalis in planktonic state; solutions HS-A and HS-B were effective in eliminating E. faecalis up to 7 McFarland, while a statistical difference (p˂0.001) was observed in reducing the bacterial load in the biofilm, based on the log10 CFU count. The final solution tested seemed not to harm the dentinal structure and was capable of causing morphological changes to the bacterial cell consistent with a hyperosmotic shock. Thus, the solutions tested could be an option to be considered as irrigating agents; nonetheless further research is required regarding its biocompatibility. Resumen. Se evaluó el efecto de una solución hiperosmótica sobre E. faecalis en forma planctónica y en forma de biofilm. A partir de formulaciones de sorbato de potasio y cloruro de sodio se obtuvieron tres soluciones hiperosmóticas (HS-A, HS-B y HS-C) con ellas se realizaron pruebas antimicrobianas contra E. faecalis en forma planctónica en concentraciones desde 0,5 hasta 7 McFarland mediante técnica de sedimentación y cuenta de UFC. Posteriormente se formó biofilm de E. faecalis por método estático por 21 días en raíces palatinas de primeros molares superiores, las cuales se prepararon biomecánicamente mediante el sistema Protaper Universal usando la solución hiperosmótica HS-B como irrigante para luego evaluar la disminución de carga bacteriana, comparando el conteo de UFC de muestras pre-instrumentación con muestras postinstrumentación. Consecutivamente las raíces fueron observadas al microscopio electrónico de barrido. En las pruebas contra microorganismos planctónicos las soluciones HS-A y HS-B fueron efectivas en eliminar E. faecalis hasta un Mc Farland de 7. En la reducción de carga bacteriana mediante conteo de UFC de los microorganismos embebidos en biofilm, se identificó una diferencia estadística (p˂0,001). La solución hiperosmótica tiene un importante efecto antibacteriano contra E. faecalis en forma planctónica y en forma de biofilm, no parece dañar la estructura dentinaria y es capaz de provocar cambios morfológicos a la célula bacteriana consistentes con shock hiperosmótico. De manera que la solución hiperosmótica parecería ser una opción a ser considerada como agente irrigante o coadyuvante de la irrigación; sin embargo, se requiere investigar más profundamente con respecto a su biocompatibilidad.